Assessment of the FAA3‐50 Polymer Electrolyte for Anion Exchange Membrane Fuel Cells. Issue 3 (23rd December 2022) - Gatto, Irene; Patti, Assunta; Carbone, Alessandra
Abstract: AEMFC is an attractive alternative to PEMFCs, due to the faster reaction kinetics that permits to use non‐platinum‐group metal catalysts and thanks to the high pH of the electrolyte allows less expensive metal hardware. In any case, the use of an alkaline exchange polymeric membrane as an electrolyte requires the development and optimization of the electrode structures and MEA. In this work, MEAs, based on FAA3‐50 commercial membrane, were developed and electrochemically characterized in single cell configuration. The hydroxylic exchange procedure of membrane and ionomer, was evaluated. The influence of different electrochemical activation procedures, and the presence of a microporous layer (MPL) in the electrodic structure were assessed. The developed MEAs were electrochemically characterized in a 25 cm 2 single cell at different operative conditions. A maximum power density of 140 mW cm −2 at 60 °C was reached with the optimized MEAs. Abstract : Polymer Electrolyte for Anion Exchange Membrane Fuel Cells : Enhancing performance by optimising electrochemical conditioning, electronic structure and anion exchange time.